1990
DOI: 10.1111/j.1559-1816.1990.tb00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Self‐Protective Behavior: Home Radon Testing

Abstract: This field experiment explored the use of informational brochures to encourage home radon testing. Homeowners (N= 271) received a radon brochure, a questionnaire, and a form for ordering a $20 radon test kit. The brochures differed in their presentations of the magnitude of the threat (varying risk likelihood and severity) and the difficulty of reducing radon levels. Some also included a detailed list of home radon risk factors. Combinations of these three variables yielded a 2 × 2 × 2 factorial design. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 18 publications
(19 reference statements)
2
72
0
2
Order By: Relevance
“…The authors concluded that people who did not test held "optimistic biases" wherein they underestimated the risks associated with exposure to radon. In another study (Weinstein, Sandman, & Roberts, 1990), researchers mailed questionnaires, informational brochures, and radon test kit order forms to 271 households in New Jersey and examined the numbers of orders for test kits according to varying presentations of the magnitude of the threat of radon (presented in the informational brochures). Although test orders were found to be unrelated to the degree of threat presented in the brochures, self-reported risk likelihood, risk seriousness, and concern were strongly correlated with intentions to test as well as test orders.…”
Section: Correlates Of Radon Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that people who did not test held "optimistic biases" wherein they underestimated the risks associated with exposure to radon. In another study (Weinstein, Sandman, & Roberts, 1990), researchers mailed questionnaires, informational brochures, and radon test kit order forms to 271 households in New Jersey and examined the numbers of orders for test kits according to varying presentations of the magnitude of the threat of radon (presented in the informational brochures). Although test orders were found to be unrelated to the degree of threat presented in the brochures, self-reported risk likelihood, risk seriousness, and concern were strongly correlated with intentions to test as well as test orders.…”
Section: Correlates Of Radon Testingmentioning
confidence: 99%
“…Because the relationship is assessed using a correlation of cross-sectional data, no conclusions are possible regarding the temporal nature between this variable and testing. However, as others have found that a knowledge of radon and radon testing is associated with future testing, it is possible that increasing knowledge about how to find out whether the home is safe from radon may predict future testing (Halpern & Warner, 1994;Kennedy, Probart, & Dorman, 1991;Weinstein et al, 1988).Because risk perception has been shown to be a critical variable with respect to radon testing behavior (Sandman & Weinstein, 1993;Weinstein et al, 1990), an examination of the accuracy of risk perception for radon exposure among rural households is warranted. Our data suggest that after adjusting for chance, the level of agreement between actual risk and perceived risk of radon exposure is quite low (21%).…”
mentioning
confidence: 99%
“…The exact wording of the questions and details of the procedures followed can be obtained from the original reports. 5,6,9,10 The dependent variable, progress toward testing, was (1).…”
Section: Integration Of Survey Datamentioning
confidence: 99%
“…For instance, many studies have assessed risk perception to test models that posit an association between risk perception and health behavior (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Other research assesses risk perception to detect errors and biases in risk judgments (15)(16)(17)(18), to assess the association between risk judgments and emotion (19)(20)(21)(22)(23)(24)(25), and to increase the accuracy of people's risk perceptions (11,(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%